Research on Integrating Sports into College Students 'Daily Lives from the Perspective of National Fitness - Chen, Bolin (Quality in Sport, 2025)
This study employs literature review, questionnaire surveys, and statistical analysis to systematically examine college students' sports lifestyles, including exercise frequency, activity types, participation motivations, and sport selection. Based on the National Fitness strategy framework, the research investigates three core elements of sports integration—time allocation, spatial accessibility, and emotional engagement—analyzing their manifestations and mechanisms within student populations. Through comprehensive analysis, the paper proposes multi-dimensional strategies and recommendations for universities, students, and enterprises. These initiatives aim to enhance sports integration in campus life, helping students improve physical fitness, achieve lasting well-being, and ultimately attain lifelong benefits through sustained participation in physical activities.